Effect of Dietary Supplementation of Tinospora cordifolia (Giloy) Powder on Performance of Broiler Chicken - Raut, Shraddha; Gadegaonkar, Ganesh; Durge, Sharad; Kulkarni, Ram; Channa, Gangaprakash; Kokate, Laxmikant (Indian Journal of Animal Nutrition, 2023)
Tinospora cordifolia (Giloy) can be effectively replace the synthetic growth promoter in broiler ration due to presence of bioactive factors and its encouraging results on the performance of broilers bird. Considering positive effect of giloy powder on the performance of broiler birds the present research work was planned to evaluate the effect of dietary supplementation of Tinospora cordifolia powder on performance of broiler chicken. The study involved 240 day old Vencobb Y 430 strain broiler chicks. The experimental chicks were randomly divided into four equal groups of 60 chicks having four replicates, containing 15 chicks in each replica. Group T0 was kept as a control and fed with standard broiler diet (BIS, 2017). Group T1, T2 and T3 was fed with standard diet (BIS, 2017) containing 0.2, 0.4 and 0.6 % giloy powder. The experiment was conducted for the period of six weeks. The results of the present study showed that the final live body weights, body weight gain and feed conversion ratio of birds from group T2 was numerically higher followed by group T3, T0 and T1, however, difference among various experimental groups was non significant. The dressing percentage and eviscerated yield percentage of birds form group T2 received diet containing  @ 0.4% giloy powder  was  significantly higher than T0, T1 and T3, however, difference among T0, T1 and T3 was comparable. It was also observed that feed treatments had no significant effect on giblet, heart, liver, gizzard, breast, drumstick and thigh weight percentage on birds from various experimental groups.  Thus, economics of broiler production indicated that supplementation of giloy powder @ 0.4% of feed was beneficial in achieving more profit due to improved performance in terms of higher live weight and better feed conversion ratio. It is concluded that supplementation of Tinospora cordifolia (giloy) powder @ 0.4% broiler feed is beneficial in improving weight gain, feed conversion ratio, carcass traits, blood biochemical profile, nutrient metabolizability and immunity parameters of birds and such supplementation is also cost  effective.